Religious Character Formation in the Digital Era Through MTSN 2 Surakarta’s Boarding School System - Achmad Zamroni; Hakimuddin Salim (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
Character education in the digital era requires a holistic and integrative approach. This study analyzes the implementation of religious character education through the boarding school program at MTsN 2 Surakarta. Using a qualitative case study design, data were collected through observation, interviews, and documentation, then analyzed using an interactive model. The findings show that religious values are internalized through a 24-hour dormitory ecosystem, structured worship habituation, regulated gadget use for one to two hours daily, Islamic digital literacy, and humanistic mentoring by musyrif and musyrifah. These strategies encourage students to move from externally controlled compliance toward moral autonomy and independent religious awareness. The integration of madrasah and dormitory systems offers a comprehensive approach to developing academically capable, spiritually resilient, socially responsible, and digitally literate students. With contextual adaptation, this model may serve as a best practice for other boarding madrasas.